Analisis pengaruh variabel makro ekonomi dalam mempengaruhi perkembangan indeks saham syariah Indonesia - Umam, Muhammad Choerul (Nur Science Institute, 2022)
This study aims to determine the effect of macroeconomic variables in influencing the development of the Indonesian Sharia Stock Index (ISSI) in 2016-2020. This type of research is quantitative based on what is obtained, namely time series data related to macroeconomic variables originating from the Central Bureau of Statistics, Bank Indonesia. The data used is secondary data which consists of several variables such as inflation, exchange rate, BI rate, gold, and oil. Multiple Linear Regression data analysis method. The results show that partially the inflation variable does not affect the Indonesian Sharia Stock Index. The exchange rate does not affect the Indonesian Sharia Stock Index. BI Rate does not affect the Indonesian Sharia Stock Index. Gold affects the Indonesian Sharia Stock Index. Furthermore, oil affects the Indonesian Sharia Stock Index.